Gating the electron transfer at a monocopper centre through the supramolecular coordination of water molecules within a protein chamber mimic. Issue 43 (13th September 2018) - Le Poul, Nicolas; Colasson, Benoit; Thiabaud, Grégory; Dit Fouque, Dany Jeanne; Iacobucci, Claudio; Memboeuf, Antony; Douziech, Bénédicte; Řezáč, Jan; Prangé, Thierry; Lande, Aurélien de la; Reinaud, Olivia; Le Mest, Yves
Abstract : Functionality of enzymes is strongly related to water dynamic processes. Abstract : Functionality of enzymes is strongly related to water dynamic processes. The control of the redox potential for metallo-enzymes is intimately linked to the mediation of water molecules in the first and second coordination spheres. Here, we report a unique example of supramolecular control of the redox properties of a biomimetic monocopper complex by water molecules. It is shown that the copper complex based on a calix[6]arene covalently capped with a tetradentate [tris(2-methylpyridyl)amine] (tmpa) core, embedding the metal ion in a hydrophobic cavity, can exist in three different states. The first system displays a totally irreversible redox behaviour. It corresponds to the reduction of the 5-coordinate mono-aqua-Cu II complex, which is the thermodynamic species in the +II state. The second system is detected at a high redox potential. It is ascribed to an "empty cavity" or "water-free" state, where the Cu I ion sits in a 4-coordinate trigonal environment provided by the tmpa cap. This complex is the thermodynamic species in the +I state under "dry conditions". Surprisingly, a third redox system appears as the water concentration is increased. Under water-saturation conditions, it displays a pseudo-reversible behaviour at a low scan rate at the mid-point from the water-free and aqua species. This third system is not observed with the Cu-tmpa complex deprived of a cavity. In the calix[6]cavity environment, it is ascribed to a species where a pair of water molecules is hosted by the calixarene cavity. A molecular mechanism for the Cu II /Cu I redox process with an interplay of (H2 O) x ( x = 0, 1, 2) hosting is proposed on the basis of computational studies. Such an unusual behaviour is ascribed to the unexpected stabilization of the Cu I state by inclusion of the pair of water molecules. This phenomenon strongly evidences the drastic influence of the interaction between water molecules and a hydrophobic cavity on controlling the thermodynamics and kinetics of the Cu II /Cu I electron transfer process.